2016
DOI: 10.1021/jacs.6b08790
|View full text |Cite
|
Sign up to set email alerts
|

TiO2–ZnS Cascade Electron Transport Layer for Efficient Formamidinium Tin Iodide Perovskite Solar Cells

Abstract: Achieving high open-circuit voltage (V) for tin-based perovskite solar cells is challenging. Here, we demonstrate that a ZnS interfacial layer can improve the V and photovoltaic performance of formamidinium tin iodide (FASnI) perovskite solar cells. The TiO-ZnS electron transporting layer (ETL) with cascade conduction band structure can effectively reduce the interfacial charge recombination and facilitate electron transfer. Our best-performing FASnI perovskite solar cell using the cascaded TiO-ZnS ETL has ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
223
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 229 publications
(240 citation statements)
references
References 33 publications
15
223
1
1
Order By: Relevance
“…On the other hand, FA‐based hybrid perovskites have better solubility than all‐inorganic perovskites. According to the summary in Table 1, no spin coating with solvent‐engineering was used in Cs‐based perovskites due to their poor solubility, but in the case of FA counterparts, most good results28, 56, 57 originated from solvent‐engineering resulted in excellent morphology. Second, mixing organic cations at A position seems an effective method to improve devices performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, FA‐based hybrid perovskites have better solubility than all‐inorganic perovskites. According to the summary in Table 1, no spin coating with solvent‐engineering was used in Cs‐based perovskites due to their poor solubility, but in the case of FA counterparts, most good results28, 56, 57 originated from solvent‐engineering resulted in excellent morphology. Second, mixing organic cations at A position seems an effective method to improve devices performance.…”
Section: Discussionmentioning
confidence: 99%
“…The author has concluded that the SnF 2 cannot only improve interfacial energy alignment but also increase stability to electron beam damage. Nowadays, most Sn‐based perovskites films prepared by solution deposition need additional SnF 2 to get good performance,47, 48, 57, 58, 73 including the recent (FA) 0.75 (MA) 0.25 SnI 3 based PSCs with the highest PCE of 8.12% 56. Additionally, Ma et al134 claimed that SnF 2 as the inhibitor of Sn 2+ oxidation in the MASnI 3 film could increase the fluorescence lifetime up to 10 times and give longer carrier diffusion lengths >500 nm, compared with pristine MASnI 3 films.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%
See 3 more Smart Citations